Development of a cross-cultural HPV community engagement model within Scotland. (June 2017) - Carnegie, Elaine; Whittaker, Anne; Gray Brunton, Carol; Hogg, Rhona; Kennedy, Catriona; Hilton, Shona; Harding, Seeromanie; Pollock, Kevin G; Pow, Janette
Objective: To examine cultural barriers and participant solutions regarding acceptance and uptake of the human papillomavirus (HPV) vaccine from the perspective of Black African, White-Caribbean, Arab, Indian, Bangladeshi and Pakistani young people. Methods: In total, 40 young people from minority ethnic communities in Scotland took part in a qualitative study, involving seven focus groups and four paired interviews, to explore their views and experiences of the HPV vaccine. Using critical discursive psychology, the analysis focused on young people's accounts of barriers and enablers to information, access and uptake of the HPV vaccination programme. Results: Participants suggested innovative strategies to tackle intergenerational concerns, information design and accessibility, and public health communications across diverse contexts. A cross-cultural community engagement model was developed, embracing diversity and contradiction across different ethnic groups. This included four inter-related strategies: providing targeted and flexible information for young people, vaccine provision across the life-course, intergenerational information and specific cross-cultural communications. Conclusion: This is the first HPV cross-cultural model inductively derived from accounts of young people from different ethnic communities. We recommend public health practitioners and policymakers consider using the processes and strategies within this model to increase dialogue around public engagement, awareness and receptivity towards HPV vaccination.